The Intensity of Use of Social Networking Applications on Self-confidence - Yuliana, Dewi (Department of Guidance and Counseling, FIP, Undiksha, 2022)
This study was intended to determine the effect of the intensity of using the Tik Tok application with self-confidence in students at the State University of Semarang. This research uses correlational quantitative method. The sampling technique used is simple random sampling with a population of 1170 people, the number of samples is 265 people. The data analysis technique used a simple linear regression test. The results of this study indicate that there is a significant positive effect of the intensity of using the tik tok application on self-confidence. Based on the results of this study, it is recommended that lecturers hold activities by utilizing social media such as Tik Tok, Instagram, Facebook and others which are currently being used by students. As a student, self-confidence is needed both in terms of lectures and in terms of society. So it can be concluded that the intensity of using the tik tok application greatly affects the self-confidence of FIP UNNES students, so if the intensity of using the tik tok application on students is high, the confidence in students will be high as well.